In Situ Formation of Bi2MoO6-Bi2S3 Heterostructure: A Proof-Of-Concept Study for Photoelectrochemical Bioassay of l-Cysteine - Xiao, Hui-Jin; Liao, Xiao-Jing; Wang, Hui; Ren, Shu-Wei; Cao, Jun-Tao; Liu, Yan-Ming (Frontiers in Chemistry, 2022)
A novel signal-increased photoelectrochemical (PEC) biosensor for l-cysteine (L-Cys) was proposed based on the Bi2MoO6–Bi2S3 heterostructure formed in situ on the indium–tin oxide (ITO) electrode. To fabricate the PEC biosensor, Bi2MoO6 nanoparticles were prepared by a hydrothermal method and coated on a bare ITO electrode. When L-Cys existed, Bi2S3 was formed in situ on the interface of the Bi2MoO6/ITO electrode by a chemical displacement reaction. Under the visible light irradiation, the Bi2MoO6–Bi2S3/ITO electrode exhibited evident enhancement in photocurrent response compared with the Bi2MoO6/ITO electrode, owing to the signal-increased sensing system and the excellent property of the formed Bi2MoO6–Bi2S3 heterostructure such as the widened light absorption range and efficient separation of photo-induced electron–hole pairs. Under the optimal conditions, the sensor for L-Cys detection has a linear range from 5.0 × 10−11 to 1.0 × 10−4 mol L−1 and a detection limit of 5.0 × 10−12 mol L−1. The recoveries ranging from 90.0% to 110.0% for determining L-Cys in human serum samples validated the applicability of the biosensor. This strategy not only provides a method for L-Cys detection but also broadens the application of the PEC bioanalysis based on in situ formation of photoactive materials.